Seroprevalence and risk factors associated with anaplasma phagocytophilum infection in horses in egypt - Mohamed MARZOK; Hattan S. GATTAN; Ibrahim ALBOKHADAIM; Mohammed H. ALRUHAILI; Mohamed SALEM; Abdelfattah SELIM (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Anaplasma phagocytophilum is a zoonotic obligate intracellular pathogen, that infects horses and is transmitted by Ixodes ticks. The seropositivity for this pathogen does not necessarily associate with clinical signs. Limited data about the epidemiology of A. phagocytophilum in horses in Egypt are available. The purpose of the study was to determine the seroprevalence of A. phagocytophilum in Egyptian horses in three Egyptian governorates and to assess the associated risk factors for infection. A total of 395 serum samples from suspected horses raising in three Egyptian governorates at Northern Egypt were examined using SNAP®4DX® ELISA test. Overall, the seroprevalence of A. phagocytophilum was 11.1% (44/395), with highest rate found in Giza governorate 15.7%. The seroprevalence of A. phagocytophilum increased significantly in older animals, in thoroughbred horses and during summer. The multivariate logistic regression model revealed that age, thoroughbreds, summer season and presence of ectoparasites were identified as risk factors for A. phagocytophilum infection in horses. The results of this study confirmed the presence of antibodies against A. phagocytophilum in Egyptian horses. Thus, regular monitoring and genetic identification of pathogens are critical for implementing an effective control program and reducing public health risks.